Analysis of Underhand Serve Ability in Volleyball Instruction for Grade XI Students at SMAN 1 Kepahiang - Noria Fitri; M. Bangkit Satrio; Agung Setiawan; Melan Saputra Jaya; Alfalif Danesa; Feby Elra Perdima (Educative Sportive, 2025)
This study aims to determine the relationship between waist flexibility and smash skills among volleyball extracurricular athletes at SMAN 08 Bengkulu City. This type of research is quantitative with a correlational approach. The population in this study were all members of the volleyball extracurricular at SMAN 08 Bengkulu City, totaling 30 athletes, while the sampling technique used total sampling. The instrument used to measure waist flexibility was the back arch test, and smash skills were measured using the Volleyball Smash Test (AUBERT). The data analysis technique used the Product Moment correlation test and significance test (t-test) at the level of $α = 0.05$. The results showed the correlation coefficient value (r_hitung) of 0.682, which means there is a strong positive relationship between the two variables. The t-test results showed that t_hitung(4.52) > t_table (2.04), which means the relationship is significant. The coefficient of determination (R^2) of 0.465 indicates that waist flexibility provides a real contribution of 46.5% to smash skills. The conclusion of this study is that there is a positive and significant relationship between waist flexibility and smash skills in volleyball extracurricular athletes at SMAN 08 Bengkulu City. Coaches are advised to integrate programmed waist flexibility training to optimize athletes' attack performance.